Modified Peham-Amreich vaginal hysterectomy technique for nonprolapsed uterus - Sotelo Salgueiro, Gonzalo (2015)
OBJECTIVE: To report the vaginal hysterectomy technique in non-prolapsed uterus; adapted from the original technique of Peham-Amreicht and modified. DESIGN: Descriptive document in 8 consecutive steps of the surgical technique, documented with photographs of each step. The description includes the right position for the surgery, the special instruments required, the surgical assistant's role and the preparation for the surgery. PLACE. Centro Hospitalario Pereira Rossell, Clínica Ginecotocológica "C", Prof. Dr. José Carlos Cuadro. CONCLUSIÓN: The vaginal hysterectomy in non-prolapsed uterus is a simple, echeloned and easily reproducible technique.